The Geopolitics of Revenge and Justice in Agatha Christie’s Murder on the Orient Express - K. C., Chandra Bahadur (The Saraswati Review, 2024)
Geopolitics deals with the role of geography in politics. It is related to the power that geography provides to the actors. Literature also includes geography (setting), which happens to be of great importance in power relations. A fictional work explores the role of geopolitics in the activities of the characters. Agatha Christie’s murder mystery novel Murder on the Orient Express covers the geopolitics of revenge and justice. The geography of Eastern Europe helps the characters seek revenge and justice for a past act of injustice. This research deals with the geopolitics of revenge and justice which is an intrinsic subject of the study of this novel and it has not been analyzed yet. The research question of this research is: how does geopolitical situation help people take revenge and provide justice for an unjust crime? The research claims that geopolitics has a great role in providing the chance for revenge and justice to the victim for whom the state is unable to do so. The geopolitics of Yugoslavia supports the murderers to take revenge on Rachett and give revenge to Armstrong's family. America is an advanced and powerful country where the relatives of the Armstrong family cannot take revenge and give justice to that family, then they choose the geography of Yugoslavia which is a powerless, backward East European country. It is a hinterland geographically where the police force cannot spread its duty all over its territory. When the train reaches this area, the murder is done because the murderers think neither the police nor the detective would be on the train in that locality. They choose Yugoslavia for the crime because they can exercise power to take revenge on the murderer and give justice to the victim's family.